BUDAYA DEMOKRASI DI SULAWESI SELATAN: PERSPEKTIF STRUKTURASI - Albintani, Muchid (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This paper was presented as an attempt to understand the relationship of culture anddemocracy in the contemporary era [political reform] in perspective Structuration in SulawesiSelatan. Cultural relations and democracy as a political system becomes an important era ofreforms ongoing regime. In this context, political culture can be a pattern for rebuilding ademocratic political behavior, especially that coming, raised and developed from the values ofthe local community, such as in Sulawesi Selatan. From this culture can be the foundation tobuild democracy ?patterned? local. Based on this argument paper is aimed at, [i] Identify andanalyze the interaction of the instruments ?culture of democracy? in the contemporary SulawesiSelatan. [i]. Formulating a contemporary democratic culture in South Sulawesi.To help explain and answer relationship with the democratic culture used the theory ofDemocracy, Political Culture and Structuration. The review of this paper shows that [i] Instrumentsand cultural interaction of democracy that exists in Sulawesi Selatan, Wajo Eclectic is aform of government, a special selection mechanism that leaders and representatives tiered,based on the relationship of the people and leaders of law as well as agreements made together.Furthermore, the interaction between these instruments indicate if the form of government,election mechanism as well as representatives and leaders of government?s relationshipwith its people have significance to the structure [political institution], not the actor or elitewith ties to the past. [ii] Based on these conditions, the formulation of political culture in theera of political reform [contemporary era] in Sulawesi Selatan is characterized by [a] Thestrong primordial and paternalism and, [b] Culture conflictual still strong, do not show thecultural values inherited from the previous., Based on this argument appears that the structureremain more influential actor who should have the value of integrity and independence.